Engineered mesoporous biochar derived from rice husk for efficient removal of malachite green from wastewaters. (March 2022) - Tsai, Chen-Yu; Lin, Pei-Ying; Hsieh, Shu-Ling; Kirankumar, Rajendranath; Patel, Anil Kumar; Singhania, Reeta-Rani; Dong, Cheng-Di; Chen, Chiu-Wen; Hsieh, Shuchen
Graphical abstract: Highlights: Rice husk derived biochar modified (RHMB) by hydrothermal auxiliary alkali. RHMB exhibited improved performance in removing Malachite green (MG). RHMB was efficient for MG removal from saline and non-saline wastewaters. Major adsorption contacts were H bonding, π-π interactions at pH 6. The maximum adsorption capacity of RHMB obtained was 373.02 mg g −1 . Abstract: Extremely soluble Malachite green (MG) acts as potential carcinogen for aquatic life in polluted aqueous environments. Current study aims to modify rice husk derived biochar to improve its removal efficiency for MG from MG-containing wastewaters. The hydrothermal alkali activation was effective for preparing modified biochar (RHMB) from native biochar (RHB) derived from rice husk. After modification, surface area and pore volume of RHMB was determined respectively 434.62 m 2 g −1 and 287.28 cm 3 g −1, significantly improved from native RHB values 21.764 m 2 g −1 and 65.53 cm 3 g −1 . Pseudo second order kinetic model fitted well. RHMB exhibits an equilibrium adsorption capacity of 373.02 mg g −1 . RHMB showed an excellent MG removal ability and was not susceptible to ion interference even at highly saline environments. It has exhibited 96.96 ± 1.17% removal efficiency of MG and is expected to be used as potential adsorbent for MG remediation from aquaculture wastewater and other MG containing industrial wastewaters.